INTEGRASI PROGRAM DINIYAH DALAM KURIKULUM MERDEKA DI SMP ISLAM AS-SAKINAH SIDOARJO - Uroidli, Ali; Jannah, Zahrotul; Sahri, Iksan Kamil (Universitas Islam Lamongan, 2024)
This study aims to explore and analyze the implementation and impact of the Integrated Diniyah Program at As-Sakinah Islamic Junior High School in Sidoarjo using a mixed method approach that integrates qualitative and quantitative aspects. A total of 110 Grade 7, 8 dan 9 students were the main subjects of this study. Qualitative data from interviews and observations were analyzed using the Miles & Huberman approach, while quantitative data from questionnaires were analyzed using statistical methods such as validity, reliability, correlation, simple regression, and T test. The results of the analysis show that the Integrated Diniyah Program not only affects religious understanding, but also significantly contributes to student learning achievement. The T test shows a significant effect of 5% obtained t table value of 1.66 between Diniyah Madrasah Education and Learning Achievement, indicating that both have a real influence.